Molecular mechanism of the spider toxin κ-LhTx-I acting on the bacterial voltage-gated sodium channel NaChBac - Xiao, Zhen; Li, Yaqi; Zhao, Piao; Wu, Xiangyue; Luo, Guoqing; Peng, Shuijiao; Liu, Hongrong; Tang, Cheng; Liu, Zhonghua (Frontiers in Pharmacology, 2022)
The bacterial sodium channel NaChBac is the prokaryotic prototype for the eukaryotic Nav and Cav channels, which could be used as a relatively simple model to study their structure-function relationships. However, few modulators of NaChBac have been reported thus far, and the pharmacology of NaChBac remains to be investigated. In the present study, we show that spider toxin κ-LhTx-1, an antagonist of Kv4 family potassium channels, potently inhibits NaChBac with an IC50 of 491.0 ± 61.7 nM. Kinetics analysis revealed that κ-LhTx-1 inhibits NaChBac by impeding voltage-sensor activation. Site-directed mutagenesis confirmed that phenylalanine-103 (F103) in the S3-S4 extracellular loop of NaChBac was critical for interacting with κ-LhTx-1. Molecular docking predicts the binding interface between κ-LhTx-1 and NaChBac and highlights a dominant hydrophobic interaction between W27 in κ-LhTx-1 and F103 in NaChBac that stabilizes the interface. In contrast, κ-LhTx-1 showed weak activity on mammalian NaV channels, with 10 µM toxin slightly inhibiting peak currents of NaV1.2-1.9 subtypes. Taken together, our study shows that κ-LhTx-1 inhibits the bacterial sodium channel, NaChBac, using a voltage-sensor trapping mechanism similar to mammalian NaV site 4 toxins. κ-LhTx-1 could be used as a ligand to study toxin-channel interactions in native membrane environments given that the NaChBac structure was successfully resolved in a nanodisc.